Exploration of carbon reduction in new municipal power systems - Ye, Jichao; Zhang, Hanbing; Hu, Xinwei; Feng, Hua; Xu, Yonghai; Ji, Aoying (Frontiers in Energy Research, 2024)
In response to China’s goal of “carbon peak and carbon neutrality”, a large number of new energy sources are connected to the power grid, and Chinese cities are also accelerating the construction of new power systems led by new energy. Taking Lishui City as an example, this paper constructs a low-carbon emission reduction evaluation system to evaluate the carbon reduction effectiveness of the new power system. This paper first introduces the basic technical characteristics of the new power system, and introduces in detail the key technologies involved in the construction of the new power system in Lishui. Then, the projects implemented by Lishui City in promoting the new power system and the current achievements were briefly summarized. After that, a new electric carbon traceability model of Lishui power system was constructed to carry out carbon traceability and carbon tracking for the municipal power grid. Finally, a low-carbon emission reduction evaluation system was constructed, and a number of evaluation indicators were proposed to evaluate the carbon reduction effectiveness of Lishui’s new power system, and the zero-carbon evaluation index was calculated through the historical data of Lishui, and the results showed that the new power system in Lishui City achieved remarkable results in carbon reduction and emission reduction.